2016
DOI: 10.1007/s10546-016-0199-9
|View full text |Cite
|
Sign up to set email alerts
|

Early Warning Signals for Regime Transition in the Stable Boundary Layer: A Model Study

Abstract: The evening transition is investigated in an idealized model for the nocturnal boundary layer. From earlier studies it is known that the nocturnal boundary layer may manifest itself in two distinct regimes, depending on the ambient synoptic conditions: strongwind or overcast conditions typically lead to weakly stable, turbulent nights; clear-sky and weak-wind conditions, on the other hand, lead to very stable, weakly turbulent conditions. Previously, the dynamical behaviour near the transition between these re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 75 publications
4
26
0
1
Order By: Relevance
“…The theoretical background behind this behavior was demonstrated by van de Wiel et al (). They show that the sudden regime transition can be understood in terms of the Minimum Wind speed for Sustainable Turbulence (MWST) theory (van de Wiel et al, ; Van Hooijdonk et al, ). If the wind speed is less than this minimum, the sensible heat flux is unable to compensate for the energy loss of the surface, which causes the near‐surface inversion to increase rapidly.…”
Section: Introductionmentioning
confidence: 81%
“…The theoretical background behind this behavior was demonstrated by van de Wiel et al (). They show that the sudden regime transition can be understood in terms of the Minimum Wind speed for Sustainable Turbulence (MWST) theory (van de Wiel et al, ; Van Hooijdonk et al, ). If the wind speed is less than this minimum, the sensible heat flux is unable to compensate for the energy loss of the surface, which causes the near‐surface inversion to increase rapidly.…”
Section: Introductionmentioning
confidence: 81%
“…In vSBL, the near surface continuous turbulence can cut off and the atmosphere decouples mechanically from the surface (Banta et al , 2007). This was explained by conceptual models in Derbyshire (1999) and van de Wiel et al (2007) and using direct numerical simulations in van Hooijdonk et al (2017). In such conditions, the radiative cooling of air may even become the dominant thermodynamic process (Estournel and Guedalia, 1985), even though some remnants of dynamic mixing of heat can persist, like intermittent bursts (e.g van de Wiel et al , 2003) or internal waves (Zilitinkevich et al , 2008; Sun et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the transition in the SBL was associated with a characteristic value of the Obukhov parameter z/L (with z the height above the surface and L the Obukhov length; Monin 1970) or a Richardson number. Recently, doubt was cast on the suitability of these parameters to mark a transition of the global character of the SBL from weakly stable (WSBL) to very stable (VSBL) (Grachev et al 2013;van Hooijdonk et al 2015;Monahan et al 2015]). As an alternative, van used the existence of a maximum in the sensible heat flux transport in the SBL (Taylor 1971;Malhi 1995;van de Wiel et al 2007) to introduce a new dimensionless ratio coined the ''shear capacity.''…”
Section: Introductionmentioning
confidence: 99%
“…Using field observations, van and Monahan et al (2015) showed that this parameter broadly separates the VSBL from the WSBL. In a DNS of a Couette flow, van Hooijdonk et al (2017b) showed that turbulence collapses when this ratio is less than a critical value.…”
Section: Introductionmentioning
confidence: 99%